Altered sex‐specific mortality and female mating success: ecological effects and evolutionary responses. Issue 5 (23rd May 2017) - Degen, Tobias; Hovestadt, Thomas; Mitesser, Oliver; Hölker, Franz
Abstract: Theory predicts that males and females should often join the mating pool at different times (sexual dimorphism in timing of emergence [SDT]) as the degree of SDT affects female mating success. We utilize an analytical model to explore (1) how important SDT is for female mating success, (2) how mating success might change if either sex's mortality (abruptly) increases, and (3) to what degree evolutionary responses in SDT may be able to mitigate the consequences of such mortality increase. Increasing male pre‐mating mortality has a non‐linear effect on the fraction of females mated: The effect is initially weak, but at some critical level a further increase in male mortality has a stronger effect than a similar increase in female mortality. Such a change is expected to impose selection for reduced SDT. Increasing mortality during the mating season has always a stronger effect on female mating success if the mortality affects the sex that emerges first. This bias results from the fact that enhancing mortality of the earlier emerging sex reduces female–male encounter rates. However, an evolutionary response in SDT may effectively mitigate such consequences. Further, if considered independently for females and males, the predicted evolutionary response in SDT could be quite dissimilar. The difference between female and male evolutionary response in SDT leads to marked differences in the fraction of fertilized females under certain conditions. Our model may provide general guidelines for improving harvesting of populations, conservation management of rare species under altered environmental conditions, or maintaining long‐term efficiency of pest‐control measures.